Tropical forest clearance impacts biodiversity and function, whereas logging changes structure - Marsh, Charles J; Turner, Edgar C; Blonder, Benjamin Wong; Bongalov, Boris; Both, Sabine; Cruz, Rudi S; Elias, Dafydd M O; Hemprich-Bennett, David; Jotan, Palasiah; Kemp, Victoria; Kritzler, Ully H; Milne, Sol; et al. (Science (New York, N.Y.), 2025)
The impacts of degradation and deforestation on tropical forests are poorly understood, particularly at landscape scales. We present an extensive ecosystem analysis of the impacts of logging and conversion of tropical forest to oil palm from a large-scale study in Borneo, synthesizing responses from 82 variables categorized into four ecological levels spanning a broad suite of ecosystem properties: (i) structure and environment, (ii) species traits, (iii) biodiversity, and (iv) ecosystem functions. Responses were highly heterogeneous and often complex and nonlinear. Variables that were directly impacted by the physical process of timber extraction, such as soil structure, were sensitive to even moderate amounts of logging, whereas measures of biodiversity and ecosystem functioning were generally resilient to logging but more affected by conversion to oil palm plantation.
Keywords: Biodiversity; deštný prales; zachování přírodních zdrojů; Rainforest; Forestry; Soil; stromy; lesnictví; Borneo; Trees; tropické klima; Arecaceae; biodiverzita; Tropical Climate; Conservation of Natural Resources; půda